Exploring the impact of cyberbullying and cyberstalking on victims' behavioural changes in higher education during COVID-19: a case study - Bussu, Anna (International journal of law, crime and justice, 2023)
This study explores cyberbullying and cyberstalking in higher education from the victims' perspective. It presents a novel contribution byutlising a convenience sample of students and staff in a university setting in England. Their perceptions as victims were collected through a semi-structured online survey during the COVID-19 pandemic. This temporal setting helps to explore how external traumatic events, collective restrictions, and increased internet use affect online social interactions. A quantitative method is employed to gain a deeper understanding of the complexity of human behaviour and factors that contribute to changes in the everyday lives of victims. Despite the exploratory nature of this study, the empirical insights provide valuable contributions that can inform the development of innovative best practice and evidence-based policies to support victims in higher education.